The impact of OECD-PISA results on Japanese educational policy - Tasaki, Noritomo (European Journal of Education, 2017)
The author describes the results of PISA, including those of 2015 and Japan’s reaction, as well as their impact. Highly-ranked in PISA, Japan has always tried to improve its education system. The promotion of reading comprehension remains an important issue and low interest and motivation to learn subjects are crucial problems. The author discusses these questions and reform policies from a Japanese point of view. He explains the latest reform plan which will be implemented in 2020. The Japanese peculiarity in education is referred to in the conclusion.